5-Fluorouracil combined with cisplatin via arterial induction for advanced T-stage nasopharyngeal carcinoma: A 10-year outcome of a phase I/II study - Xiang, Li; Zheng, Yun; Ren, PeiRong; Lin, Sheng; Zhang, JianWen; Wen, QingLian; He, LiJia; Shang, ChangLing; Wu, JingBo (Frontiers in Oncology, 2022)
Background and purpose: Currently, there is no optimal dose recommendation for a 120-h continuous infusion of 5-fluorouracil via arterial cannulation for advanced T-stage nasopharyngeal carcinoma (NPC). Thus, the aim of this study was to determine the maximum tolerated dose (MDT), along with the efficacy, late adverse events, and 10-year survival outcome of 5-fluorouracil administered continuously for 120 h combined with cisplatin via the superficial temporal artery in patients with advanced T-stage NPC. Materials and methods: Fifty-one patients with histologically confirmed advanced T-stage NPC were eligible for inclusion in this clinical trial. The patients received induction chemotherapy consisting of cisplatin (20 mg/m2/d for 1–5 d) and 5-fluorouracil, administered continuously for 120 h at different dose gradients via a superficial temporal artery. To identify the MTD of 5-fluorouracil infused arterially, we employed a 3+3 design during study phase I. The initial dose administered was 200 mg/m2/d, which then was gradually escalated by 50 mg/m2/d until the MTD was reached. Following two cycles of induction chemotherapy, current radical chemoradiotherapy commenced. We assessed the efficacy, survival, toxicity, and quality of life of patients following treatment. Results: The overall response (complete response + partial response) rates following induction chemotherapy in the primary mass and lymph nodes were 100% and 100%, respectively. All 51 (100%) patients achieved T-category down-staging after intra-arterial chemotherapy. The MTD was 450 mg/m2/d for 120 h. No late neurological toxicities, such as brain stem injury, temporal lobe necrosis, and spinal cord injury, were observed. The 5- and 10-year overall survival (OS) rates were 78.0% and 71.7%, respectively, with a median OS of 131 months. Conclusion: Continuous infusion of 5-fluorouracil combined with cisplatin via the superficial temporal artery showed promising survival benefits and few toxicities in patients with advanced T-stage NPC.